2022
DOI: 10.1111/afe.12537
|View full text |Cite
|
Sign up to set email alerts
|

Net enclosures disrupt codling moth dispersal not establishment

Abstract: 1. Apple growers have pursued the use of exclusion netting to reduce pesticide inputs and maintain control of codling moth.2. It is uncertain if these nets provide a physical or behavioural behaviour, and if they prevent codling moth establishment.3. To address this, we conducted field trials testing the ability of commercial netting to exclude codling moth using small (3 trees) and large (48 trees) cages. Experiments were conducted to evaluate both the permeability by releasing marked sterile moths either ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Netting studies published thus far for apple fruit have focused on insect pest exclusion benefits in Europe ( 20 , 22 , 23 ) and North America ( 17 , 19 , 24 , 31 ). However, as noted by Onstad and Crain ( 62 ) and Fornasiero et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Netting studies published thus far for apple fruit have focused on insect pest exclusion benefits in Europe ( 20 , 22 , 23 ) and North America ( 17 , 19 , 24 , 31 ). However, as noted by Onstad and Crain ( 62 ) and Fornasiero et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented that both the apple maggot and codling moth are able to move through mesh sizes that are similar to those employed in hail netting ( 28 , 30 , 31 ). However, it is believed that the presence of netting interrupts mate-seeking behavior in the codling moth ( 22 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a study in Washington found that codling moth could be excluded by using net cages (2 × 5 mm mesh) placed around large orchard blocks ( Marshall and Beers 2021 , 2022 ). While successful at reducing fruit injury initially, these cages did allow a few individuals through, and over time moths were able to establish a population within these blocks ( Marshall and Beers, 2023 ). Additionally, the investigators found that while the cages effectively excluded large, flying insects, smaller and less mobile insects such as aphids were consistently more abundant inside cages than outside ( Marshall and Beers 2021 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both the apple maggot and codling moth are able to move through mesh sizes that are similar to those employed in hail netting (variable mesh size: 7.4 × 3 mm, 6 × 1.8 mm, etc.) ( Sauphanor et al 2012 , Chouinard et al 2022 , Marshall and Beers 2023 ). It is believed that effective exclusion is due to both small mesh sizes and interference with mate-seeking behavior in the codling moth ( Tasin et al 2008 , Marshall and Beers 2023 ).…”
Section: Introductionmentioning
confidence: 99%